2023
DOI: 10.7554/elife.83012
|View full text |Cite
|
Sign up to set email alerts
|

Firing patterns of ventral hippocampal neurons predict the exploration of anxiogenic locations

Abstract: The ventral hippocampus (vH) plays a crucial role in anxiety-related behaviour and vH neurons increase their firing when animals explore anxiogenic environments. However, if and how such neuronal activity induces or restricts the exploration of an anxiogenic location remains unexplained. Here, we developed a novel behavioural paradigm to motivate rats to explore an anxiogenic area. Male rats ran along an elevated linear maze with protective sidewalls, which were subsequently removed in parts of the track to in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…However, there is no discernible effect on SYP expression in these areas [ 29 ]. While 17-OHPC exposure induces anxiety-like behaviors in mice, it does not trigger autism-like behaviors, suggesting that progestin exposure may modulate women’s mood, including anxiety, fear, and depression [ 4 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no discernible effect on SYP expression in these areas [ 29 ]. While 17-OHPC exposure induces anxiety-like behaviors in mice, it does not trigger autism-like behaviors, suggesting that progestin exposure may modulate women’s mood, including anxiety, fear, and depression [ 4 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, the precision of spatial coding diminishes along the dorsoventral axis of the HPC 810 . Second, neurons in more ventral parts of the HPC exhibit a stronger association with the emotional valence of locations 1114 and odors 15 as compared to the dHPC. Furthermore, optogenetic studies further suggest that specific pathways between the basolateral amygdala (BLA) and vHPC are recruited during anxiety and fear-related behaviors 12,1618 .…”
mentioning
confidence: 99%
“…This result failed to support our initial hypothesis, and was surprising given the ample published evidence for a role of vHPC in controlling anxiety and fear behavior. 12,14,16,17,22 A possible explanation for the dHPC freezing-associated inhibition would be related to the motor, rather than the emotional, aspects of freezing. Previous work had shown that activity in dHPC is modulated more by animals' speed than vHPC.…”
mentioning
confidence: 99%